Redress for historical injustices in the United States on reparations for slavery, Jim Crow, and their legacies - Martin, Michael; Yaquinto, Marilyn 1956- (Duke University Press, 2007)
An exceptional resource, this comprehensive reader brings together primary and secondary documents related to efforts to redress historical wrongs against African Americans. These varied efforts are often grouped together under the rubric "reparations movement," and they are united in their goal of "repairing" the injustices that have followed from the long history of slavery and Jim Crow. Yet, as this collection reveals, there is a broad range of opinions as to the form that repair might take.